2015
DOI: 10.1186/s12879-016-1346-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between human leukocyte antigen class II and pulmonary tuberculosis due to mycobacterium tuberculosis in Uganda

Abstract: Background Mycobacterium tuberculosis (Mtb) is reported to infect about a third of the world’s population but only 10 % are thought to develop active tuberculosis (TB) disease. Host immunity regulated by human leukocyte antigens (HLA) is an important determinant of the outcome of the disease. Here we investigate HLA class II gene polymorphisms in susceptibility to TB, and whether particular HLA class II alleles were associated with TB in Uganda.MethodsHIV negative patients with pulmonary TB (n = 43) and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Remarkably, the latter was not significantly associated with pulmonary TB in Croatians (cs/ cn=438/1008), but it was significantly linked to increased risk for the disease in both, Icelandic population (p<3 × 10 -7 , cs/cn=3686/287427) and Russians (p<5 × 10 -4 , cs/cn=5530/5607). Recent case-control studies from other groups, despite using much lower number of individuals, corroborated the role of HLA class II in affecting the risk for TB in Ugandan (HLA DQB1 * 03:03, cs/cn=43/42) [8] and Brasilian Amazon populations (HLA DRB1 * 04, cs/cn=316/306) [9]. Together, the data strongly suggest that poorly-Mycobacterium tuberculosisbinding HLA class II alleles might contribute to developing TB by being one of the many risks among multifactorial genetic hallmarks of tuberculosis.…”
Section: Introductionmentioning
confidence: 93%
“…Remarkably, the latter was not significantly associated with pulmonary TB in Croatians (cs/ cn=438/1008), but it was significantly linked to increased risk for the disease in both, Icelandic population (p<3 × 10 -7 , cs/cn=3686/287427) and Russians (p<5 × 10 -4 , cs/cn=5530/5607). Recent case-control studies from other groups, despite using much lower number of individuals, corroborated the role of HLA class II in affecting the risk for TB in Ugandan (HLA DQB1 * 03:03, cs/cn=43/42) [8] and Brasilian Amazon populations (HLA DRB1 * 04, cs/cn=316/306) [9]. Together, the data strongly suggest that poorly-Mycobacterium tuberculosisbinding HLA class II alleles might contribute to developing TB by being one of the many risks among multifactorial genetic hallmarks of tuberculosis.…”
Section: Introductionmentioning
confidence: 93%
“…HLA also controls the secretion of cytokines and modulates the immune response by cytokine genes on haplotypes. Susceptibility alleles on HLA may also lead to GD/HT by preferentially regulating the Th2/Th1 pathways, respectively [710]. …”
Section: Cytokines and Cytokine-related Genes In Aitdmentioning
confidence: 99%
“…185 Approximately one-third of the global population has latent, asymptomatic TB, 185 and although those individuals only have a 10% chance of developing active TB disease, 186 risk is larger in individuals with compromised immune systems owing to conditions such as diabetes or HIV infection. Caused by the bacteria Mycobacterium tuberculosis , TB begins with fever, weight loss and coughing.…”
Section: Introductionmentioning
confidence: 99%
“…189 Many studies have reported associations between susceptibility and resistance to TB and several HLA loci and/or alleles 190, 191, 192, 193 and allele frequencies of these markers are known to vary between ethnic groups. 194 One recent study from Uganda suggests the HLA-DQB1*03:03 allele may be associated with resistance to TB, 186 but much work needs to be done between African populations to assess population-specific allele-frequency differences and/or corresponding pharmacogenomic outcomes. Moreover, the contributions of rare variants with potentially large effects or multiple genes of small effect warrant systematic investigation.…”
Section: Introductionmentioning
confidence: 99%